АНАЛІЗ ДОВГОСТРОКОВИХ ФАКТОРІВ ВПЛИВУ НА ДОХОДИ БЮДЖЕТІВ ТЕРИТОРІАЛЬНИХ ГРОМАД - Мартьянов, Максим Петрович (Науковий журнал «Світ фінансів», 2017)
Мартьянов М. П. Аналіз довгострокових факторів впливу на доходи бюджетів територіальних громад. На основі емпіричних даних про бюджети територіальних громад Вінницької області проаналізовано взаємозв’язки між величиною надходжень до цих бюджетів та основними економічними факторами, що їх обумовлюють. Зроблено висновки про те, що на базовому рівні найбільш важливими напрямами політики щодо збільшення доходів бюджетів є політика підтримки підприємництва та політика, спрямована на розвиток сільських територій. Мартьянов М. П. Анализ долгосрочных факторов влияния на доходы бюджетов территориальных общин. На основе эмпирических данных о бюджетах территориальных общин Винницкой области проанализированы взаимосвязи между величиной поступлений в эти бюджеты и главными экономическими факторами, которые их определяют. Сделан вывод о том, что на базовом уровне наиболее важными направлениями политики по увеличению доходов бюджетов есть политика поддержки предпринимательства и политика, ориентирована на развитие сельских территорий. Martjanov M. Analysis of long-run impacts on local government budgets reveneus. Introduction. Improving the efficiency of local government financial support is the strategic Ukrainian budget policy objective. Discrepancy of financial resources and scope of powers assigned to local governments is the precondition of inter budgetary relations reforming. There is a need to create conditions for increasing their own revenues, improve the efficiency of budget spending, provide quality public services to the population. Purpose. To analyze the influence of long-term trends factors on the Vinnitsa region local budgets’ revenues, to predict Vinnitsa region local budgets’ main indicators by 2022 and to identify areas of local government financial support improvement. Results. During last 10 years more than 75% in local revenues were consists of revenues from the personal income, payment for land and single tax. Before the adoption amendments to the Budget Code a system of local government financial support was dependent on the state budget. In a significant number of budget revenues share of transfers was 60–70%. If we assume that by 2022 will not be major changes in tax and budget legislation, it is expected that the share of revenues and expenditures of local budgets in GRP will remain approximately at the same level as in 2014. Approaches to the revenue and expenditure base of local budgets and the mechanism of intergovernmental relations has been changed as a result of amendments to the Budget Code, which were entered into force on 1 January 2015 In the software package Gretel it was determined that in 2004–2008 such factors as the volume of industrial production; the number of industrial enterprises; capital investments; the average monthly wage made the greatest impact on local budgets’ revenues, but in 2009–2014 the biggest impact had such factor as the number of businesses. Conclusion. Results of the analysis show the relation between the size of local budgets with economic parameters such as the value of industrial production, average wages, the number of businesses, amount of capital investment. Structural reforms, promotion of investment, business development are determined as the ways of improvement local government financial support.